Internal Prose Contestations in the 5th-century AH Andalusia: Between Innovation and Imitation - CHAOUI, Asma (Journal of Science and Knowledge Horizons, 2025)
This article explores the concept of prose contestations, their origins, development, and importance in Andalusian literature, while attempting to shed light on the areas of innovation and creativity in them, as well as to prove the worthiness of the subsequent text, which may equal the previous text in its artistic value or may surpass it at times, since the real objective of contestation is not limited to imitation, but to expansion and refinement. Prose contestations contributed to the prosperity of artistic prose in the 5th century AH in Andalusia. Among the aspects of this innovation are the contestations of Al-Zahriyat, Al-Matariyat, Al-Zarzuriyyat, and Al-Mu’tadhdiyat, in which the Andalusian prose writer set out in his creativity from nature, the disordered political conditions in Andalusia.